Art & copy [videorecording (DVD)] (One Club, 2010)
This film is about advertising, that traces the shift from the old boy's network of the '40s to the more "creative," story-based approach of the '60s, when dynamic young men fought conventional wisdom to create campaigns that quickly transcended mere commerce and became pop-culture sensations. The guys behind the ads--the unknown people who've so profoundly shaped our culture--all want to be seen as genius artists, not corporate executives, which is the crux of many problems with the advertising revolution. This film, like a good commercial, is propulsive, filled with eye-grabbing visuals, emotional appeals, nostalgia, and instantly recognizable imagery--a greatest-hits survey of commercials that conquered the world.